Evaluating attitudes and perception of HIV and AIDS related stigma among health care professionals in Vhembe District of Limpopo Province - Ramaano, Pfananani Nancy (University of Limpopo ( Turfloop campus), 2011)
Objectives: To assess the extent of HIV and AIDS related stigma among health care professionals, to identify factors that cause attitudes and perception towards HIV and AIDS related stigma and to determine if HIV and AIDS influence stigma. Study design: A descriptive cross sectional survey. Settings: Tshilidzini Hospital in Limpopo Province, South Africa. Subjects: A total of two hundred and sixty five health care professionals participated in the study. The study employed convenience sampling, when collecting data. The majority of health care professionals were females (77.7%). The average age of participants was 39.5 years with a standard deviation of 9.6. Outcome measures: Subject’s demographic information was determined by use of questionnaire. Age, gender educational level and race were included. Attitudes and perception towards HIV and AIDS patients were also assessed. Analysis: Data were analyzed by SPSS windows version 15.0. Means and frequencies were calculated. ANOVA and T test were employed to assess the comparison of attitudes between health care professionals. Findings: The results showed that the majority of health care professionals do not have negative attitudes towards people living with HIV and AIDS. Out of 265 health care professionals, 69% agreed that they needed to eliminate shame and rejection associated with HIV and AIDS, and 84% indicated that they needed more training to be more sensitive to the needs of people living with HIV and AIDS.Conclusion: Findings from the study showed high positive attitudes and perception among health care professionals towards people living with HIV and AIDS. Government should make provision of protective clothing a priority to reduce the perceived risk of HIV infection. Government should also introduce HIV and AIDS education at the primary level of health care.
Thesis (MPH.) --University of Limpopo, 2011
Keywords: HIV; AIDS; Stigma; Health care professionals; 362.1969792; HIV (Virus); AIDS (Disease) -- South Africa; Nurses -- Attitudes; Clinical psychology